INFORMATION AND ANALYTICAL SUPPORT OF FINANCIAL SERVICES ON THE SECURITIES MARKET - Matsuk , Z.A. (The actual problems of regional economy development, 2018)
The article analyzes the informational and analytical support of financial services on the securities market. A systematic approach in determining the main areas of construction of the information infrastructure of the securities market and the established nature of the links and relationships between its individual elements has been used. It is proved that the most important role in the financial assets trading belongs to information. The main elements of it are identified and characterized: information on issuers of securities, securities statistics, data on stock indexes and information of rating agencies